3D printing of robotic soft grippers: toward smart actuation and sensing - Goh, Guo Dong (2022)
Unlike traditional hard grippers, soft robotic grippers are commonly made of soft materials so that the soft grippers can produce motion via elastic deformations of their compliant components. The advantages of compliance allow soft grippers to effectively eliminate shocks caused by hard contact, which usually occurs when a hard robotic gripper manipulates a hard object. Until now, the soft robotic grippers are able to operate numerous objects with irregular geometries and different textures. Besides, with the help of embedded sensors, soft robotic grippers have facilitated the growing automation of many tasks, which are thought to be far too delicate for robotic manipulation. This paper reviews the advancement in soft robotic grippers. The paper first introduces the actuation technologies followed by the design and fabrication techniques. The use of 3D printing techniques in the fabrication of the soft gripper is also discussed. The Review then highlights the challenges and future outlook in the fabrication of soft grippers and sensors.